2013
DOI: 10.1016/j.pneurobio.2012.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Insights into cortical mechanisms of behavior from microstimulation experiments

Abstract: Even the simplest behaviors depend on a large number of neurons that are distributed across many brain regions. Because electrical microstimulation can change the activity of localized subsets of neurons, it has provided valuable evidence that specific neurons contribute to particular behaviors. Here we review what has been learned about cortical function from behavioral studies using microstimulation in animals and humans. Experiments that examine how microstimulation affects the perception of stimuli have sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 186 publications
4
105
2
1
Order By: Relevance
“…S2), as would be expected if the animals were directly detecting changes in neuronal activity and not the laser light. Shorter reaction times to cortical stimulation [∼150 ms minimum compared with ∼210 ms minimum in a visual task (23)] are further evidence that animals detect direct neuronal activation, as has been shown previously in a range of species and brain areas (24)(25)(26)(27)(28).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…S2), as would be expected if the animals were directly detecting changes in neuronal activity and not the laser light. Shorter reaction times to cortical stimulation [∼150 ms minimum compared with ∼210 ms minimum in a visual task (23)] are further evidence that animals detect direct neuronal activation, as has been shown previously in a range of species and brain areas (24)(25)(26)(27)(28).…”
Section: Resultsmentioning
confidence: 55%
“…Electrical stimulation studies cannot examine network linearity, because pulsed current has a stronger effect than sustained current (48) and because there is a complex relationship between stimulation current and evoked spike count. However, the stimulation currents used likely evoked stronger activity than our near-threshold stimulation (27,49). In fact, frequency discrimination of both sensory and direct electrical stimuli is best with intensities well above the detection threshold (50).…”
Section: Discussion Linear Population Codes Can Arise From Weak Inputmentioning
confidence: 86%
“…In fact, a more detailed neurophysiological understanding of the stimulation effects on the axons of different neurons is still lacking, and thus a different type of analysis is required to better elucidate this relationship. 21 A blinded comparison between the 2 stimulation modalities should be performed to address this issue in a more robust way. However, such a study is unlikely to be easily realized with appropriate statistical power for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that use electrical stimulation to evoke complex motor movements use less, with typical values being 300 Hz, 500 ms, and amplitudes ranging from 10 to 300 A depending on cortical area (Bruce et al 1985;Graziano et al 2002;Thier and Andersen 1998). Finally, awake behaving studies have found current detection thresholds to be around 10 A, or less with training, when intracortical microstimulation is applied to sensory cortices (Medina et al 2012;Murphey and Maunsell 2007;Ni and Maunsell 2010;O'Doherty et al 2009;Salzman et al 1990; for reviews, see Clark et al 2011;Histed et al 2013). For the parameters tested, cortical activation was dependent on both the current amplitude of a single pulse and the number of pulses.…”
Section: Effects Of Stimulation Parametersmentioning
confidence: 99%